Utilization of Arduino as Incinerator Control Using Temperature Sensor - Mohammad Ibrahim Ashari; Anis Artiyani (IJISTECH (International Journal of Information System and Technology), 2022)
The waste problem is part of the dynamics of human life. Every human activity must produce waste. Garbage is a pollution that interferes with the health and comfort of the community. Solid waste management is a challenge for developing countries, mainly due to the increase in waste generation. Garbage results in high city budget costs related to its management. One of the impacts of urban development is an increase in the volume of waste. This requires improvement of facilities and infrastructure against limited land. For this reason, good and efficient waste management is needed. In general, waste disposal that does not meet environmental health requirements can result in, among other things, breeding grounds and nests of insects and rats, becoming a source of pollution and contamination of soil, water and air, becoming a source and a place to live. live germs that endanger health. Based on this, the researchers made a tool in the form of a furnace that can be used for waste treatment and burning garbage. From the results of the overall tool testing, to obtain optimal combustion results in the mass of waste (4 Kg) and the combustion temperature setting (200 oC- 300 oC) is fixed, the minimum burning time is 30 minutes